2013
DOI: 10.3892/mmr.2013.1352
|View full text |Cite
|
Sign up to set email alerts
|

A novel chimeric peptide binds MC3T3-E1 cells to titanium and enhances their proliferation and differentiation

Abstract: Previous studies have demonstrated that the modification of the titanium (Ti) surface of an implant with RGD (Arg‑Gly‑Asp) promotes the activity of osteoblasts. A novel Ti‑binding peptide, minTBP‑1, and a chimeric peptide, minTBP‑1‑PRGDN, have been synthesized to assist the fixing of RGD to Ti. In our previous study, minTBP‑1‑PRGDN demonstrated favorable affinity for Ti surfaces and facilitated the adhesion of MC3T3‑E1 cells. The aim of the present study was to evaluate the effect of this chimeric peptide on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Alkaline phosphatase (ALP) is closely involved in cell differentiation and cell division; it is also involved in calcification via regulating phosphate transport [ 20 ]. Because it increases osteoblast differentiation, ALP is used as an osteoblast biomarker [ 21 ]. Here, we observed that after 2 weeks of LF-I and LF-II treatment, ALP-positive MC3T3-E1 cells increased significantly over control-group amounts.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline phosphatase (ALP) is closely involved in cell differentiation and cell division; it is also involved in calcification via regulating phosphate transport [ 20 ]. Because it increases osteoblast differentiation, ALP is used as an osteoblast biomarker [ 21 ]. Here, we observed that after 2 weeks of LF-I and LF-II treatment, ALP-positive MC3T3-E1 cells increased significantly over control-group amounts.…”
Section: Discussionmentioning
confidence: 99%
“…The first category often discussed when addressing this challenge is osteogenic cells such as osteo-progenitor cells, osteoblasts, and osteocytes. , Although these cells are still derived from mesenchymal cells, their previous commitment to the osteogenic lineage allows them to begin secreting bone matrix components almost immediately upon implantation. , Thus, osteogenic markers such as type 1 collagen and alkaline phosphatase are expected to be present sooner into the regenerative process, therefore improving the rate of bone healing . In recent years, the MC3T3 preosteoblastic cell line has become a standard model regarding lineage committed cells for applications in bone tissue engineering. , In many studies with chitosan-based cross-linked scaffolds, these cells have thus been included for evaluation of osteogenic differentiation and mineralization potential in the materials. For example, in a genipin cross-linked chitosan-gelatin scaffold with GO incorporated, Selaru et al were able to use MC3T3 cells to demonstrate enhanced osteogenic differentiation and mineral deposition compared to scaffolds without GO .…”
Section: Cell Encapsulation In Chitosan Cross-linked Scaffoldsmentioning
confidence: 99%
“… 33 In recent years, the MC3T3 preosteoblastic cell line has become a standard model regarding lineage committed cells for applications in bone tissue engineering. 185 , 186 In many studies with chitosan-based cross-linked scaffolds, these cells have thus been included for evaluation of osteogenic differentiation and mineralization potential in the materials. For example, in a genipin cross-linked chitosan-gelatin scaffold with GO incorporated, Selaru et al were able to use MC3T3 cells to demonstrate enhanced osteogenic differentiation and mineral deposition compared to scaffolds without GO.…”
Section: Cell Encapsulation In Chitosan Cross-linked Scaffoldsmentioning
confidence: 99%
“…These studies have shown that the efficiency of osseointegration acquisition was improved by immobilization technologies, i.e. recombinant bone morphogenetic protein (BMP) [24,25], RGD [26,27], chimeric [28], and antimicrobial peptide [29,30] and Sema3A-contained chitosan film [31], onto Ti surface. On the other side, the number of reports on modification of titanium surface that aimed to the long-term stability of the implant to solve the problems such as peri-implantitis and loss of osseointegration has gradually increased.…”
Section: Discussionmentioning
confidence: 99%